2019
DOI: 10.5194/amt-12-4019-2019
|View full text |Cite
|
Sign up to set email alerts
|

The new BELUGA setup for collocated turbulence and radiation measurements using a tethered balloon: first applications in the cloudy Arctic boundary layer

Abstract: Abstract. The new BELUGA (Balloon-bornE moduLar Utility for profilinG the lower Atmosphere) tethered balloon system is introduced. It combines a set of instruments to measure turbulent and radiative parameters and energy fluxes. BELUGA enables collocated measurements either at a constant altitude or as vertical profiles up to 1.5 km in height. In particular, the instrument payload of BELUGA comprises three modular instrument packages for high-resolution meteorological, wind vector and broadband radiation measu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(88 citation statements)
references
References 47 publications
6
82
0
Order By: Relevance
“…If compared to a study from Antarctica (Jokinen et al, 2018) or laboratory studies by Dunne et al (2016) from the CERN CLOUD (Cosmics Leaving Outdoor Droplets) chamber, our calculated H 2 SO 4 concentration is 10 to 30 times lower than that from previous studies. On the other hand, the results of this study are in agreement with a study by Ehn et al (2007), who studied the relationship between particle hygroscopicity and sulfuric acid concentration in boreal forest. The authors reported that the concentration of H 2 SO 4 , corresponding to 15 and 20 nm particle HGFs of 1.34 and 1.46, was in a range of 10 7 molecules cm −3 .…”
Section: Indirect Evidence Of the Composition Of Newlysupporting
confidence: 93%
“…If compared to a study from Antarctica (Jokinen et al, 2018) or laboratory studies by Dunne et al (2016) from the CERN CLOUD (Cosmics Leaving Outdoor Droplets) chamber, our calculated H 2 SO 4 concentration is 10 to 30 times lower than that from previous studies. On the other hand, the results of this study are in agreement with a study by Ehn et al (2007), who studied the relationship between particle hygroscopicity and sulfuric acid concentration in boreal forest. The authors reported that the concentration of H 2 SO 4 , corresponding to 15 and 20 nm particle HGFs of 1.34 and 1.46, was in a range of 10 7 molecules cm −3 .…”
Section: Indirect Evidence Of the Composition Of Newlysupporting
confidence: 93%
“…Added value of the OCEANET measurements can be obtained when they are accompanied by additional observations. During the two-week ice floe camp performed in the frame of PASCAL, a tethered balloon site was set up for turbulence and radiation observations (Egerer et al, 2019) and a network covering 15 pyranometers to determine the spatial variability of the solar radiation was installed (Barrientos Velasco et al, 2019). In the context of this study, the turbulence as determined from the three-dimensional wind vector measured with high temporal resolution of several tens of Hertz by an ultrasonic anemometer attached to the tether of the balloon was used.…”
Section: Auxiliary Instrumentationmentioning
confidence: 99%
“…If this criteria was matched within more than one wavenumber interval the mean of all ε i for one spectrum was calculated. In order to evaluate the EDR estimated by cloud radar measurements, it was compared to EDR derived from the tethered balloon (Egerer et al, 2019). The time periods used for deriving EDR from the tethered balloon was 15 minutes, during which it was located at a constant height above ground.…”
Section: Edr From Vertical-stare Doppler Velocity Power Spectramentioning
confidence: 99%
See 2 more Smart Citations